KOGNITIF SOSIAL TUNAWISMA DI KOTA SEMARANG - Fuadah, Laily (IJTIMAIYA: Journal of Social Science and Teaching, 2019)
Homelessness life shows a social behavior that is quite interesting to study, especially in their learning results of imitating behavior towards their social environment. The aim of this research is to determine the social learning of homelessness in Semarang city by using Albert Bandura’s social cognitive theory, which emphasizes on the modelling (imitating behavior). This research uses a qualitative method with a phenomenological approach. The reason of the researcher uses this approach since the researcher is directly involved in understanding social learning and research phenomena. Through this design, this research is expected to provide maximum results to the readers. Data collection technique uses direct observation, interviews, and document studies. Data analysis technique uses Spradley model and Hubberman Miles model which go through several stages, including data collection, data reduction, data presentation, and drawing conclusions. The result of this research shows that homelessness has an imitating behavior in accordance with the five basic assumptions of Bandura’s social cognitive theory. The social cognitive shown by the homelessness is caused by the attitude of adjustment based on the place and social life as an effort to survive on the streets